(untitled) (Research, Society and Development, 2023)
Theories consist of a set of principles and concepts that convey a systemic view of certain phenomena, aiming to describe and explain their chainings. In nursing, they are used to base professional practice and define its practical purpose, constituting important references for care models. This study aims to reflect on the applicability of Dorothea Orem’s General Nursing Theory of Self-Care Deficit in the co-production of nursing care. This is a theoretical-reflective essay, of an interpretative nature, derived from studies concerning the discipline of Theoretical-Philosophical Conceptions in the Nursing and Health Care Process of the Graduate Program in Nursing at the Federal University of Santa Catarina. The reflective methodology made possible to highlight self-care from the author’s point of view, the conceptions about the co-production of patient-centered care and the relationship between the theorist’s concepts and the co-production framework. It was found that Dorothea Orem’s General Nursing Theory of Self-Care Deficit, when applied in the co-production of nursing care can originate shared care management; the systematic use of the co-production framework; nursing prescriptions and interventions focusing on self-care and health promotion actions; nursing guidelines with the potential for co-production of care and improvement of self-care; and the improvement of implemented nursing interventions.